Transparency : the material history of an idea - Jütte, Daniel (Yale University Press, 2023)
Transparency is a mantra of our day. It is key to the Western understanding of a liberal society. We expect transparency from, for instance, political institutions, corporations, and the media. But how did it become such a powerful—and global—idea? From ancient glass to Apple’s corporate headquarters, this book is the first to probe how Western people have experienced, conceptualized, and evaluated transparency. Daniel Jütte argues that the experience of transparency has been inextricably linked to one element of Western architecture: the glass window. Windows are meant to be unnoticed. Yet a historical perspective reveals the role that glass has played in shaping how we see and interpret the world. A seemingly “pure” material, glass has been endowed, throughout history, with political, social, and cultural meaning, in manifold and sometimes conflicting ways. At the same time, Jütte raises questions about the future of vitreous transparency—its costs in terms of visual privacy but also its ecological price tag in an age of accelerating climate change.